Lucas 4.16-30: um ideário programático do evangelho - Bueno, Clovis Henrique (2015)
The pericope of Luke 4: 16-30 seems to be a literary and theological synthesis of the third Gospel. Based on a rereading of a pericope of the Gospel of Mark, of texts from Isaiah and, eventually of other sources, Luke transforms the received tradition into a program for the ministry of Jesus aiming at the public of his writings. The work is organized into three chapters: introductory issues, semantic analysis of the pericope and an analysis of the redactional intervention of the evangelist in the material received. Among the themes which Luke highlights from this program is the offering of the Gospel to the poor, the guidance of the Holy Spirit, the rejection of the Gospel in his own country and the opening of the Gospel to the gentiles, themes which pervade the two works of Luke.